2019
DOI: 10.4314/ijbcs.v13i2.35
|View full text |Cite
|
Sign up to set email alerts
|

The fall armyworm <i>Spodoptera frugiperda</i> (J.E. Smith), a new pest of maize in Africa: biology and first native natural enemies detected

Abstract: The fall armyworm (FAW), Spodoptera frugiperda is a real threat to food security. It is able to totally destroy the cereal crops in a country. It can cause famine in Sub-Saharan Africa where cereals are subsistence crops. Reported in Africa in 2016, the FAW succeded to colonize 47 countries in one year. Its migration capacities wich are of around 100 km per night can allow it have fully infest a country like Senegal (ca 200 000 km²) in less than a week. The FAW is very difficult to fight because resistant to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 36 publications
(35 reference statements)
3
44
1
6
Order By: Relevance
“…curvimaculatus in Kenya (Sisay et al 2018; and Ch. bifoveolatus in Ghana, Benin, Senegal and Tanzania (Agboyi et al 2020;Koffi et al 2020;Ngangambe and Mwatawala 2020;Tendeng et al 2019), in Zambia we have recorded two species. This could have some implication for interspecific competition, therefore, further studies are needed to understand the interaction and ecological niches of both species, mainly if classical biological control is considered in the future with Ch.…”
Section: Discussionmentioning
confidence: 53%
“…curvimaculatus in Kenya (Sisay et al 2018; and Ch. bifoveolatus in Ghana, Benin, Senegal and Tanzania (Agboyi et al 2020;Koffi et al 2020;Ngangambe and Mwatawala 2020;Tendeng et al 2019), in Zambia we have recorded two species. This could have some implication for interspecific competition, therefore, further studies are needed to understand the interaction and ecological niches of both species, mainly if classical biological control is considered in the future with Ch.…”
Section: Discussionmentioning
confidence: 53%
“…bifoveolatus. Based on photos provided in [20], these were likely also the two larval parasitoids recovered from S. frugiperda in Senegal, even though the authors identified them as Campoletis sp. and Chelonus sp., respectively.…”
Section: Parasitoid Complex and Parasitism Of S Frugiperda In Ghana mentioning
confidence: 99%
“…However, there is presently limited available information on the natural enemies of S. frugiperda in Africa. Some authors studied the parasitoid complex of the pest in Ethiopia, Kenya, Tanzania [18,19] and Senegal [20]. In addition, the platygasterid egg parasitoid Telenomus remus Dixon was recorded in Côte d'Ivoire, Benin and Niger [21] and the biology of the braconid larval parasitoid (Coccygidium luteum Brullé) has recently been studied in Ghana [22].…”
Section: Introductionmentioning
confidence: 99%
“…dengan cara menghitung jumlah larva yang ditemukan kemudian diambil untuk identifikasi di Laboratorium Fakultas Pertanian, Universitas Flores mengacu kepada hasil penelitian Tendeng et al (2019).…”
Section: Metodologiunclassified